Prescription patterns in psychiatric compulsory care: polypharmacy and high-dose antipsychotics - Kaikoushi, Katerina; Karanikola, Maria; Middleton, Nicos; Bella, Evanthia; Chatzittofis, Andreas (My University, 2021)
Antipsychotic polypharmacy and prescription of high-dose antipsychotics are often used for the treatment of psychotic symptoms, especially in compulsory psychiatric care although there is lack of evidence to support this practice and related risks for patients.
Keywords: compulsory; high-dose antipsychotics; involuntary; Polypharmacy